2021
DOI: 10.1371/journal.pone.0248505
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and complications of autologous fat grafting to the eyelids and periorbital area: A systematic review and meta-analysis

Abstract: Background In recent years, autologous fat grafting (AFG), also known as fat transfer or lipofilling, has been widely performed for periorbital rejuvenation and defect correction, although the evidence regarding its efficacy and safety is still lacking. Besides, with respect to the periorbital region, it is invariably the earliest appearance area of the facial aging phenomenon. Therefore, a systematic review and meta-analysis is needed to evaluate the efficacy and safety of this technique. Methods A literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Thus, the surgical method and approach must be planned according to the patients' anatomical characteristics to improve surgical results. Common complications of infraorbital fat transplantation include insufficient volume or an over-correction of volume, local excessive bloating leading to obvious midface sagging after transplantation, infection, granuloma and inflammation, vascular embolism with a loss of vision, or cerebral infarction (13)(14)(15). In the mid-face, facial arteriovenous terminal branches traverse the muscular fascial system near the side of the nose.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the surgical method and approach must be planned according to the patients' anatomical characteristics to improve surgical results. Common complications of infraorbital fat transplantation include insufficient volume or an over-correction of volume, local excessive bloating leading to obvious midface sagging after transplantation, infection, granuloma and inflammation, vascular embolism with a loss of vision, or cerebral infarction (13)(14)(15). In the mid-face, facial arteriovenous terminal branches traverse the muscular fascial system near the side of the nose.…”
Section: Discussionmentioning
confidence: 99%
“…We divided the facial areas into the malar eminence, infraorbital area, and nasolabial fold area to assess 4 items: volume consistency, softness, irregularity, and overall satisfaction. Each item was evaluated on a 5-point scale ranging from 1 to 5 points (1=extremely dissatisfied, 2=dissatisfied, 3=neutral, 4=satisfied, and 5=extremely satisfied), (Supplemental Table 1, Supplemental Digital Content 2, http://links.lww.com/SCS/E518) as previously described 11–14. The questionnaire was administered twice 3 and 6 months after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Each item was evaluated on a 5-point scale ranging from 1 to 5 points (1 = extremely dissatisfied, 2 = dissatisfied, 3 = neutral, 4 = satisfied, and 5 = extremely satisfied), (Supplemental Table 1, Supplemental Digital Content 2, http://links.lww.com/SCS/ E518) as previously described. [11][12][13][14] The questionnaire was administered twice 3 and 6 months after surgery. FIGURE 1.…”
Section: Patient Evaluation and Criteriamentioning
confidence: 99%
“…Coleman fat, which is processed using a standard technique comprising aspiration, centrifugation, and grafting, is effective for periorbital grafting [ 14 16 ]. However, other studies of fat grafting in the periorbital region with Coleman fat have reported various postoperative complications, including persistent edema, fatty nodules, cysts, calcification, and asymmetric fat displacement [ 3 , 17 , 18 ]. In 2016, a novel fat-derived stromal vascular fraction (SVF) gel that retains a higher percentage of the stromal vascular fraction and stem cells was developed by Feng Lu and his team.…”
Section: Introductionmentioning
confidence: 99%